MICROSATELLITE-BASED GENETIC VARIATION IN Rhizophora apiculata AND Rhizophora mucronata FROM EAST KALIMANTAN - Adristi Shafa Widyasari; Abdul Razaq Chasani; Istiana Prihatini; Tri Atmoko; Mukhlisi; Burhanuddin Adman; Bina Swasta Sitepu (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- Microsatellite markers were used to study population genetic variation in Rhizophora- Molecular systematic analysis showed moderate genetic diversity with low heterozygosity- Population genetic structure was dominated by within-population variation (AMOVA)- Phenetic analyses revealed weak clustering among Rhizophora populations- Genetic patterns supported connectivity within Rhizoporaceae populations in East KalimantanABSTRACTMangroves of the family Rhizophoraceae are pantropical, with the genus Rhizophora forming a major component of tropical mangrove ecosystems. Rhizophora apiculata and Rhizophora mucronata are widely distributed in the Paser region, Balikpapan Bay, and the Mahakam Delta of East Kalimantan, Indonesia. This study examined genetic diversity and population structure of both Rhizophora species using simple sequence repeat (SSR) markers. The results showed moderate genetic diversity but relatively low heterozygosity in both species. Most genetic variation occurred within populations, as indicated by AMOVA, while R. apiculata exhibited lower genetic differentiation among populations and lacked private alleles, and R. mucronata showed higher population differentiation and possessed private alleles, suggesting localized genetic variation. Cluster and principal coordinate analyses revealed extensive overlap among populations for both species, indicating weak population structure and ongoing gene flow across the study area. Overall, the findings suggest that populations of R. apiculata and R. mucronata in East Kalimantan function as genetically connected units rather than as strongly differentiated populations. These results highlight the importance of maintaining habitat connectivity and protecting genetically unique populations to support the long-term resilience and sustainable management of mangrove genetic resources in East Kalimantan.